Design and implement a self-managed computer network for electronic exams and sharing - Mokhaled N. Abdullah; Ihab A. Satam; Raid W Daoud; Suhail N. Shihab; Haider A. Kamel (Institute of Advanced Engineering and Science, 2020)
To implement electronic exams and material resources sharing (which is usually limited), an operating base is must be available for trading information and correspondence management. In this paper, self-managed computer networks, no server was designed. This network aims to share information and correspondence management between the laboratory`s computers. A specific software called Packet tracer used for designing and simulating the network, also for choosing the right medium and install the IP address so that a maximum of data flowing with minimum time and no data loss can be achieved. A class-C IP address was selected since it is the famous class and it doesn`t need any special equipment. Also it has a wide range of of computers in case of expanding the network. We didn`t use a wireless medium to protect the network from hacking. The network was based on an Ethernet medium and a star-connection between the computers with an average signal distributer. An excellent result was achieved after testing the network with a low error percentage, as shown in the result section of this paper.